Peran Adaptasi Game (Gamifikasi) dalam Pembelajaran untuk Menguatkan Literasi Digital: Systematic Literature Review - Sari, Dwi Novita; Alfiyan, Ahmad Rifqy (Pendidikan Teknologi Informasi Universitas Bumigora, 2023)
This research is a systematic literature review that aims to analyze the role of game adaptation or gamification in learning to strengthen digital literacy. Using the SLR method, this research identifies, synthesizes, and analyzes relevant scientific articles about the use of game adaptations in the context of learning digital literacy. This review explores how game elements and principles, such as point systems, challenges, competitions, and prizes, are applied in learning to improve students' digital literacy. In addition, this study analyzes the impact of using game adaptations on motivation, engagement, active participation, and the development of students' digital literacy skills. The implications of these SLR findings provide important insights for educators, curriculum developers, and researchers in designing effective learning strategies to increase students' digital literacy.